Female labour fource in Brazil: inside the statistics - Saffioti, Heleieth I. B. (Universidade Estadual Paulista / UNESP, 2009)
Theoretically speaking, this article has been conceived from the feminist point of view, which is here understood as a new scientific and political-perspective. Therefore, we refuse the radical feminism position, according to which gender relationships constitute the primary principle able to explain the capitalist societies social structure, as well as the simpletons who reduce the complex texture of class societies to class struggles. Feminism as a scientific and political perspective takes into account not only these two antagonisms, but also their interrelations. Therefrom derives the conception of this type of society in terms of patriarchy-capitalism and not as patriarchal capitalism. This theoretical framework allows the examination, through history, of the unequal incorporation of women in the Brazilian labour force. If during the 1872-1982 period the data concerning this phenomenon suffered changes, on the other hand, they also demonstrate the preservation of discriminations against women. That is, the majority of working women goes on occupying low positions, receiving low wages even when they perform the same occupational function, accumulating wage work and domestic services. These phenomena, as well as those related to them, can only be eliminated by the struggle against patriarchy-capitalism, aiming the complete destruction of this symbiosis which creates conditions for the domination-exploration of almost all by a few and women by men.